Penegakan Hukum Tindak Pidana Di Bidang Cukai Diwilayah Hukum Kantor Wilayah DJBC Sumatera Bagian Timur - Ramadian Fajar Satria (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Customs plays a vital role in supervising the flow of goods entering and leaving customs areas, as well as in the collection of import and export duties, as regulated in Article 2 paragraph (1) of the Indonesian Customs Law. This study employs an empirical method through observations and interviews at the Customs Office of Eastern Sumatra to examine the effectiveness of monitoring specific goods and preventing smuggling. The findings reveal that measures such as sea patrols, land patrols, and market operations have had a tangible impact in reducing the entry of illegal goods, particularly in South Sumatra, thereby supporting the optimization of customs law enforcement.